2014
DOI: 10.5897/ajps2013.1041
|View full text |Cite
|
Sign up to set email alerts
|

An ethnobotanical study of medicinal plants in Debre Libanos Wereda, Central Ethiopia

Abstract: An ethnobotanical study of medicinal plants in Debre Libanos Wereda, in central Ethiopia, was carried out from October 2008 to June 2009. A total of 60 informants were interviewed that include knowledgeable farmers, monks, nuns, herbalist farmers and full time herbalists. A total of 83 medicinal plants classified under 77 genera and 46 families were collected. Asteraceae were the most prominent family (7) species and (6) genera, followed by Fabaceae and Lamiaceae that contain four species in three genera each.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 23 publications
10
33
0
Order By: Relevance
“…Ethnobotanical studies conducted in different parts of the country [9,25,26] reported similar results. Majority of the remedies in the study District were reported to be taken internally/orally followed by smearing on the skin.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Ethnobotanical studies conducted in different parts of the country [9,25,26] reported similar results. Majority of the remedies in the study District were reported to be taken internally/orally followed by smearing on the skin.…”
Section: Discussionmentioning
confidence: 57%
“…Many studies conducted in different parts of Ethiopia also showed that leaves are used more frequently than any other parts [6,25,26]. As compared to other parts, damage inflicted on medicinal plants due to harvest of leaves is very minimal [27].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used plant parts for herbal preparations were leaves (40%), followed by roots (30.91%) and bark (12.73%) ( Figure 2b). Common utilization of leaves in the preparation of remedies can be a result of the relative easiness of finding this plant part as compared with the others (Getaneh and Girma, 2014). Most of the remedies (84.37%) which are used for an ailment of tonsillitis were prepared from fresh plant materials (Figure 3a).…”
Section: Growth Forms and Parts Of Medicinal Plant Speciesmentioning
confidence: 99%
“…Ethnobotany is a scientific study of how peoples interact with plant resources within their ethnic groups. It gives particular emphasis on traditional cultures (Getaneh and Girma, 2014) and plays an important role in the discovery of new products from plants (Katewa, 2009). Plants provide a variety of use for every life form (Schippmann et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been largely employed as an insect repellent against fleas and mosquitos and as antimalarial [47,50,52,53]. Inhalation of the smoke of burnt stems and leaves is used against evil eye [48,51] and its juice, diluted with water, is drunk for treatment of stomach ache, vomiting, nausea, diarrhea, and dysentery [46,51]. In the same geographical area, the juice of O. tomentosa and O. fruticosa has been similarly used against diarrhea [46], and the latter also against ascariasis [46] and tonsillitis [48].…”
Section: Traditional Usesmentioning
confidence: 99%